Competencies of Librarians: Inputs Towards a Proposed CPD Plan - Dabu, Maria Nimfa (Journal of Interdisciplinary Perspectives, 2024)
Continuous Professional Development (CPD) ensures that professionals can be updated with the new trends and practices in their profession. Continuous learning in the workplace is essential for a professional's development and ensuring quality delivery. This study examined the competency levels of librarians at State Universities and Colleges (SUC) in Region 3, Philippines, about the National Competency- Based Standards for Filipino Librarians (NCBS-FL) and the Philippine Qualification Frameworks for Librarians (PQF-L). The research employed a mixed methods design. A total of forty-four (44) librarians from SUC Main Campuses took part in a study using a research instrument that was adapted from the work of Lanzuela (2018) and Fernandez and Buenrostro (2015). The profiles of the participants were described using frequency and percentage. For the analysis of their self-evaluation on the NCBS-FL, PQF-L, and the impact of the CPD in developing essential competencies, means and standard deviations were calculated, along with ANOVA and T-Tests for inferential analysis. The results indicated that the participants had a Proficient Level of competency in both the Personal and Professional Competencies areas, according to the NCBS-FL assessment. The participants have a Proficient Level in the Desired Minimum Professional Competencies domain but are at the Developing Level in the Advanced Professional Competencies domain. The findings show that CPD programs help participants achieve basic professional skills and develop more advanced skills. The participants faced several challenges in achieving professional growth through the CPD program. These included budget constraints, lack of support from administrators, and insufficient staffing.